Disinfection of dental root canals by cold atmospheric plasma: a systematic review and meta-analysis of dental biofilm - Sanesi, Lorenzo; Puca, Valentina; Caponio, Vito Carlo Alberto; Pinti, Morena; Balice, Giuseppe; Femminella, Beatrice; Paolantonio, Michele; Cela, Ilaria; Kaushik, Nagendra Kumar; Choi, Eun Ha; Grande, Rossella; Sardella, Eloisa; et al. (Frontiers in Oral Health, 2024)
AimThe intricate structure of the tooth root canals has a role in the colonization and biofilm formation in hidden areas that are hardly reached by standard endodontic treatments. This review aims at summarizing data from in vitro and ex vivo studies for a better understanding of the application of cold atmospheric plasma (CAP) for the disinfection of dental root canals.MethodsPubMed, Scopus, and Web of Science databases were screened. Characteristics of the included studies were extracted, and a meta-analysis on ex vivo studies was carried out to evaluate the effect of CAP on colony forming unit assay of Enterococcus faecalis (E. faecalis). The study was performed following the PRISMA 2020 guidelines.ResultsA total of 31 studies fulfilled the selection criteria. Only 2 investigations reported an indirect plasma treatment, 28 trials used direct CAP administration, while 1 study applied both methods. Most of the studies were conducted on E. faecalis using as carrier gas Helium or Argon alone or in combination with Oxygen as well air. A considerable heterogeneity among studies was found regarding treatments which varied for source type, settings, and protocols of application. Despite this, CAP showed effectiveness in reducing E. faecalis colony forming unit with a standardized mean difference of 4.51, 95% C.I. = 2.55–6.48, p-value < 0.001.ConclusionThe data demonstrated the antimicrobial effect of direct CAP application against microorganisms. In-vitro studies showed an effect that depended on the time and distance of treatment, while the meta-analysis performed on ex vivo studies showed that the effect of CAP was independent of time and distance.Systematic Review Registrationhttps://doi.org/10.17605/OSF.IO/BJ59V, identifier OSF registries.